Evolution of biomass char structure during oxidation in O2 as revealed with FT-Raman spectroscopy - Keown, D.; Li, X.; Hayashi, J.; Li, Chun-Zhu (Elsevier, 2008)
FT-Raman spectroscopy has been used to identify structural features and evaluate the structural evolution of biomass chars during gasification with air. Chars prepared from the pyrolysis of a cane trash sample with a fast particle heating rate in a novel fluidised-bed/fixed-bed reactor at 500, 700 and 900 °C were oxidised at 400 °C in air in a TGA. The data derived from the spectral deconvolution of Fourier Transform — Raman spectra suggest that the 500 °C char showed very different structural features after pyrolysis and during oxidation from the 700 and 900 °C chars, while the differences between the latter two chars were small. Preferential consumption by O2 of smaller aromatic rings and structures of somewhat aliphatic characteristics left the char more enriched with larger aromatic ring systems. The changes in char structure are in agreement with the observed reactivity measured in O2 in a thermogravimetric analyser.